SCIENCE AND TECHNOLOGY IN THE QURAN EDUCATION METHOD - Yasmansyah Yasmansyah; Lainah -; Zulfani Sesmiarni (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
Technological advances in the last three decades have shown its influence on any and all lives of individuals, society and country. It can be said that no one can escape from the influence of the development of science and technology, science and technology is not only felt by the individual, but also by the community, nation and state. Modern science and technology makes many people admire then imitate in a lifestyle without being selected in advance of any negative impacts in the future or the resulting multidimensional crisis. Islam does not hinder. The progress of science and technology is also not anti-technological goods in the past, present or future come. In the Qur'an there are many texts (verses) which encourage people to see, look, think, and observe the phenomena of the universe created by Allah SWT. interesting for investigated, researched and developed. The Qur'an challenges humans to use his mind as optimally as possible